Decolonial feminism contributions to feminist art: streets, bodies and a multitude of otherness (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
Reflecting on feminist artistic actions in the Global South implies confronting the exclusive centrality of gender markers within feminist art, as well as the absence of solid debates regarding race in the application of feminist art category. Decolonial feminism, and its attention to the co-constitutive relationship between race and gender as colonial instruments of controlling bodies, holds the potential to broaden debates around feminist art. Considering the impact that theories of performativity have on scenic arts, the text examines Un violador en tu camino, by the Las Tesis Collective (Chile), and Noite das Estrelas, by the Entidade Maré collective (Brazil), to suggest necessary fissures within the category of feminist art.
Keywords: feminist art; decolonial feminism; performativity; public space; Latin America